2019
DOI: 10.3390/ani9050236
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Partially or Completely Substituted Dietary Zinc Sulfate by Lower Levels of Zinc Methionine on Growth Performance, Apparent Total Tract Digestibility, Immune Function, and Visceral Indices in Weaned Piglets

Abstract: The study aimed to evaluate the effects of replacing zinc sulfate (ZnSO4) with a lower level of zinc methionine (ZnMet) on the growth performance, apparent total tract digestibility (ATTD) of nutrients, serum metabolites and immune functions of weaned piglets. Thirty-five weaned Duroc × Landrace × Large White male piglets (10.69 ± 0.26 kg) were randomly allotted to five diets. The control diet was supplemented with 100 mg/kg of Zn from ZnSO4, and experimental diets included 75 + 12.5, 50 + 25, 25 + 37.5, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
2
16
2
Order By: Relevance
“…The present study showed that the different Zn supplementation forms had no effect on the growth performance of piglets. Xie et al [ 9 ] also reported that there was no significant difference in the growth performance of pigs fed diets supplemented with different levels or sources of Zn. A recent study by Zhang et al found that the piglets fed with 20, 40, and 80 mg Zn/kg as zinc amino acid complex had a similar growth performance to pigs fed with 40 mg Zn/kg as ZnSO 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that the different Zn supplementation forms had no effect on the growth performance of piglets. Xie et al [ 9 ] also reported that there was no significant difference in the growth performance of pigs fed diets supplemented with different levels or sources of Zn. A recent study by Zhang et al found that the piglets fed with 20, 40, and 80 mg Zn/kg as zinc amino acid complex had a similar growth performance to pigs fed with 40 mg Zn/kg as ZnSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Research evidence has indicated that organic Zn sources is recommended widely in animals because of their higher bioavailability than inorganic Zn [ 7 , 8 ]. Xie et al [ 9 ] reported that piglets with body weight of 11 kg fed diet supplemented with a lower dose of Zn-Met replacing 100 mg/kg ZnSO 4 had no negative effects on nutrient digestibility, growth performance, and serum metabolites, and indeed, supplementing 50 mg ZnSO 4 plus 25 mg Zn-Met to piglets exerted the beneficial effects of Zn digestibility and immune functions. Furthermore, Li et al [ 10 ] found that in 38 weeks old laying hens dietary Zn-Met had beneficial effect on Zn accumulation in tissues, intestinal morphology, and the mRNA expression of metallothionein (MT) in the intestinal as compared to ZnSO 4 supplementation in the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 116 ] reported that combinations of Zn oxide and tannins (ZnO + hydrolysable tannins) improved the antioxidant capacity and digestive enzymes of pigs. Organic zinc (Zn glycinate and Zn methionine) also influences the pigs’ antioxidant status and helps maintain a healthy immune system [ 117 , 118 ]. In another study, supplementation of Se and vitamin E at high levels attenuated HS’s impact on the intestinal barrier integrity of pigs, associated with a depletion of OS, as assessed by decrease in antioxidant enzymes [ 119 ].…”
Section: Mitigation Of Heat-stress-induced Intestinal Permeability By Antioxidantsmentioning
confidence: 99%
“…The capability of antioxidants to protect the intestinal barrier integrity and increase the levels of antioxidant enzymes can lead to better gut health, intestinal function, alleviation of endotoxemia and OS. Such abatement on the intestinal integrity components signifies better nutrient digestion and absorption which can be summed up as a better production performance of pigs under HS, as supported by the pigs’ manifestation of better growth, intestinal barrier function, enhanced immune function and improved antioxidant system [ 115 , 118 , 119 ].…”
Section: Mitigation Of Heat-stress-induced Intestinal Permeability By Antioxidantsmentioning
confidence: 99%
“…Using mineral amino acid chelates as feed additives in pig nutrition could increase mineral bioavailability and enhance mineral tissue storage. The stable structures of mineral chelates prevent undesirable interactions with feed compounds in the digestive tract, and using active transport pathways via metallotransporters across enterocytes contributes to better mineral absorption and utilisation in the animal body [5,7,8]. Moreover, the elimination of mineral interference with some dietary nutrients, such as phytates or fibres, could improve the mineral efficacy.…”
Section: Introductionmentioning
confidence: 99%